2016
DOI: 10.1021/acssuschemeng.6b02366
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of the Acid-Rich Fraction of Bio-oil by Catalytic Hydrogenation-Esterification

Abstract: The complex composition, high degree of unsaturation, and strong corrosiveness of bio-oil make direct catalytic upgrading problematic due to coking and device corrosion, and therefore, proper pretreatment is required. In this study, catalytic hydrogenation-esterification was identified as an efficient pretreatment method for bio-oil upgrading, and the hydrogenation-esterification behavior of typical compounds found in the acid-rich fraction of bio-oil over Cu/ SBA-15 catalyst was investigated. It was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 63 publications
(124 reference statements)
0
24
0
Order By: Relevance
“…2017 Chen et al 2017 . The most common practice is to add a catalyst during the pyrolysis process to selectively control the distribution of pyrolysis products and further increase the yield of the desired target product, thereby improving the bio-oil quality.…”
Section: Introductionmentioning
confidence: 99%
“…2017 Chen et al 2017 . The most common practice is to add a catalyst during the pyrolysis process to selectively control the distribution of pyrolysis products and further increase the yield of the desired target product, thereby improving the bio-oil quality.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, both oxygen (removed as H 2 O in esterification) content and acidity are decreased, without requiring any additives such alcohols and with lower hydrogen consumption. 24,44…”
Section: Resultsmentioning
confidence: 99%
“…23 More recently, hydrotreating of methanol solutions containing furfural, hydroxyacetone, guaiacol, and acetic acid over Cu/SBA-15 has shown to lead to the formation of diverse saturated esters and alcohols. 24…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that reaction pressure could affect both hydrogenation and cracking processes: the elevation of hydrogen pressure could improve the hydrogenation efficiency of bio-oil components (Mortensen et al 2011); pressurized cracking favored the formation of liquid hydrocarbons, but this influence became insignificant when the pressure was above 2 MPa (Wang et al 2013b). 4 MPa was selected in this work because the author's previous study using this pressure successfully achieved the hydrogenation of aldehyde group , which is also a typical unsaturated functional group in bio-oil, and similar pressures were also used in the mild hydrogenation of bio-oil components (Vispute et al 2010;Chen et al 2016). The weights of hydrogenation and the cracking catalysts were both 2 g. The weight hourly space velocity of liquid feedstock was 2 h -1 , in terms of the weight of the hydrogenation catalyst.…”
Section: Catalytic Reactionmentioning
confidence: 99%